A combined Ricardian and Heckscher-Ohlin model of comparative advantage - Edward E. Leamer (Institute for Advanced Studies (IHS), 1995)
The Heckscher-Ohlin theory and the Ricardian theory of international commerce traditionally have been treated as separate conceptual frameworks, but a growing body of empirical work is relying on both simultaneously and calls for an integrated theory. This paper combines the Heckscher-Ohlin model and Ricardian model into a single unified framework and offers supporting evidence for both Heckscher-Ohlin effects and Ricardian effects in OECD specialization patterns.
Keywords: F11; F14; O14; 330; comparative advantage; technology adoption; trade; Außenwirtschaftstheorie; Theorie